Impact of loading protocol of a mandibular single implant-supported complete denture on oral health-related quality of life over a period of 5 years: A randomized controlled trial - Waltenberger, Lukas Laurentius Erik; Reissmann, D. R.; Blender, S.; Fritzer, E.; Heydecke, G.; Kappel, Stefanie; Mundt, T.; Schierholz, C. V.; Stiesch, M.; Wolfart, S.; Yazigi, C.; Kern, M.; et al. (Journal of dentistry, 2024)
OBJECTIVES: The aim of the present study was to assess the long-term course of OHRQoL and the impact of the loading protocol in patients receiving a single mandibular implant supporting a complete denture over a period of five years. - METHODS: In this multicenter RCT, a total of 158 edentulous patients were initially included and were randomly allocated immediately after placement of a mandibular midline implant to either immediate loading (IL) or to conventional loading (CL) with submerged healing. The assessment of OHRQoL was performed with the 49-item Oral Health Impact Profile (OHIP) at baseline and 1, 4, 12, 24, and 60 months after loading. At 5-year follow-up, 100 patients (mean age: 69.2 years; 45.0% female) with completed OHIP were available for analyses. A mixed-effects model with patients as random effect and an unstructured covariance matrix was developed to address repeated outcome measurement. - RESULTS: The OHRQoL improved substantially after loading, indicated by a decrease of mean OHIP summary scores from 51.0 points at baseline, by 14.2 (95%-CI: 9.4 - 19.1; p<0.001) points to 37.2 points at 1-month follow-up, and by continuous improvement to 20.4 OHIP points at final follow-up. Considering constant treatment effects, the loading protocol had no significant effect on OHIP scores (-3.7, 95%-CI: -9.4 - 2.2; p = 0.204). Time effect was statistically significant with -0.21 (95%-CI: -0.28 - -0.15; p<0.001) points per month. - CONCLUSION: Both the immediate and conventional loading of a single mandibular midline implant supporting a complete denture offer long-lasting high levels of OHRQoL, with no significant or clinically relevant long-term differences. - CLINICAL SIGNIFICANCE: The study firstly presents long-term data for OHRQoL by investigating the loading protocol of single mandibular implant-supported complete dentures. Since immediate loading has been associated with a reduced implant survival rate for this concept, information on patient benefits is essential for evidence-based decision making.